First results of the 2D gas electron multiplier in the dominant electron heating scenario on EAST. (29th August 2019) - Li, Erzhong; Qu, H.; Hu, L.; Cordella, F.; Claps, G.; Pacella, D.; Murtas, F.; Zhang, L.; Zhou, T.; Zhao, H.; Lin, S.; Chen, K.; et al.
Abstract: The 2D gas electron multiplier (GEM) is used to measure the chord-integrated soft x-ray radiation in the direction tangential to the magnetic field. With the Tikhonov tomography algorithm, the soft x-ray emissivity is derived considering the soft x-ray air transmission factor. The cooling factors are also determined according to the continuum and impurity line radiations. The impurity concentration is then obtained from the measured emissivity. In the dominant electron heating scenario, iron is the main impurity of which the high ionization states contribute to the total counting rate of GEM. The up-down asymmetry of concentrated impurity is observed before the plasma confinement conversion from edge localized mode (ELM)-free high confinement mode (H-mode) to ELMy H-mode. A large scale perturbation is observed which is radially elongated on the tomography plots as the electron temperature profile shows in–out asymmetry. The perturbation drives outward impurities and energy transport, reducing the impurity concentration and the electron temperature gradient in the core. The underlying instability is also discussed which shows the relevance of the macroscopic mode with the iron impurity density and electron temperature profiles.